Problematika Endorsment di Media Sosial: Kajian Maanil Hadist Batasan Aurat Muslim Hadist Riwayat Imam Ahmad dan Abu Daud - Syah, Firman; Mugiyono; M. Nur, Sulaiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In this modern era, there are many promotional strategies that can be implemented, one of which is using endorsements on social media to introduce their products to consumers. However, along with this development, there are negative impacts that are not realized in carrying out endorsement activities which we often find on social media which are not in accordance with Islamic religious law, whether carried out by men or women, namely not paying attention to the limits of their private parts and contradicting the hadith. narrated by Abu Daud regarding the limits of women's private parts and a hadith narrated by Imam Ahmad regarding the limits of men's private parts. This research aims to determine the understanding of the hadith of Abu Daud's history and the hadith of Imam Ahmad's history regarding the private parts in relation to endorsements on social media using a qualitative of library research method. The results of this research study are that understanding the hadith regarding the limits of private parts has important relevance in the context of endorsements on social media, especially for individuals who want to carry out endorsement activities according to religious teachings and design endorsement strategies that do not only focus on financial profits, but also respect the boundaries of private parts and religious values.